Characteristics and pollution indices of leachates from municipal solid waste landfills in Iranian metropolises and their implications for MSW management - Mohammad Hossien Saghi; Hojjat Nadimi; Akbar Eslami; Seyed Nadali Alavi Bakhtiarvand; Ali Oghazyan; Somayeh Setoudeh; Mohammad Sadegh Sargolzaei (Scientific Reports)
Abstract Leachate from municipal solid waste landfills poses a significant threat to aquatic ecosystems due to poor management practices. This study evaluated thirty leachate samples from Iranian metropolises using the Leachate Pollution Index (LPI). Various parameters, including BOD₅, COD, TDS, pH, EC, heavy metals, turbidity, PAHs, phthalates, and humic acid, were analysed. The BOD₅ levels ranged from 350 to 20,000 mg/L, and the COD levels ranged from 2,000 to 90,000 mg/L. The TDS content varied between 14.7 and 67 g/L, while the turbidity ranged from 15 to 186 NTU. Heavy metals were present but within standard limits. The phthalate concentrations ranged from 6 to 150.8 mg/L, and the humic acid concentrations ranged from 135 to 2,200 mg/L. Naphthalene was the most frequent hydrocarbon detected. The LPIs were less than 30 for all the samples, with the highest in Ahvaz and the lowest in the treated samples from Tehran. This study highlights the presence of persistent organic and hazardous contaminants in Iran’s municipal landfills, emphasizing the need for effective leachate treatment and improved waste management practices. Enhanced final disposal methods, increased waste recovery, and improved solid residue separation are crucial for preventing further leachate production and environmental contamination.